Nitric Oxide Turnover Under Hypoxia Results in the Rapid Increased Expression of the Plastid-Localized Phosphorylated Pathway of Serine Biosynthesis - Zafari, Somaieh; Vanlerberghe, Greg C.; Igamberdiev, Abir U. (Frontiers in Plant Science, 2022)
The plant mitochondrial electron transport chain influences carbon and nitrogen metabolism under near anoxic conditions through its involvement in the phytoglobin-nitric oxide cycle, where the respiratory chain reduces nitrite to nitric oxide (NO), followed by NO conversion to nitrate by class 1 phytoglobin. Wild type (WT) and transgenic tobacco (Nicotiana tabacum L.) with differing amounts of alternative oxidase (AOX) were used to manipulate NO generation under hypoxia, and to examine whether this in turn influenced the gene expression of two stress-related amino acid biosynthetic pathways, the plastid-localized phosphorylated pathway of serine biosynthesis (PPSB), and the γ-aminobutyric acid (GABA) shunt. Under hypoxia, leaf NO emission rate was highest in AOX overexpressors and lowest in AOX knockdowns, with WT showing an intermediate rate. In turn, the rate of NO emission correlated with the degree to which amino acids accumulated. This amino acid accumulation was associated with the increased expression of the enzymes of the stress-related amino acid biosynthetic pathways. However, induction of the PPSB occurred much earlier than the GABA shunt. This work shows that high rates of NO turnover associate with rapid gene induction of the PPSB, establishing a clear link between this pathway and the maintenance of carbon, nitrogen and energy metabolism under hypoxia.